10‐2: Student Paper: Dual‐Driver Pixel Circuit and Associated Drivers for Low‐Power OLEDoS Microdisplays. Issue 1 (28th June 2022) - Gohardehi, Sheida; Sachdev, Manoj
Abstract : This paper proposes a new low‐power driving method that reduces the number of sub‐frames and the operating frequency of drivers in a digitally‐driven display. The measurement results using this method on a 480x640 microdisplay implemented in TSMC 65 nm technology show a 38% reduction in the power consumption of the driver.